Intimate Partner Violence during Pregnancy and Postpartum Depression in Japan: A Cross-sectional Study - Takeo Fujiwara; Takeo Fujiwara; Ayano Miura (Frontiers Media S.A., 2017)
BackgroundThe impact of intimate partner violence (IPV) on postpartum depression (PPD) has been reported in various countries by many studies. However, the association between IPV and PPD in Japan has been scarce. In addition to the limited number of research on the relationship between IPV and PPD, the number of women seeking help from IPV support centers has been steadily increasing in Japan. Hence, it is of interest to explore the relationship between IPV during pregnancy and PPD in Japan.MethodsFour-page questionnaires assessing sociodemographic characteristics, women's personal situation during pregnancy, and PPD were mailed to participants prior to the checkup and collected at the checkup sites or mailed back to the health center. Of 9,707 eligible mothers, 6,590 responded to a questionnaire at a 3- or 4-month infant health checkup (response rate: 68%). Verbal and physical IPV from partners was assessed with two questions in the questionnaire. Logistic regression analysis was conducted. PPD was evaluated using the Edinburgh Postnatal Depression Scale (EPDS) with a cutoff score of 8/9.ResultsPartners' verbal and physical abuse during pregnancy was significantly associated with PPD after adjusting for possible confounders. Specifically, odds ratios (ORs) of PPD for women who had been verbally abused by their partners during pregnancy at a frequency of "often" were 4.85 (95% CI, 2.23-10.55). ORs of PPD among women who had been physically abused by their partners during pregnancy at a frequency of "sometimes or often" were 7.05 (95% CI, 2.76-17.98). A positive dose-response relationship between both types of IPV and PPD was statistically significant (both p < 0.001). In addition, about 80% of physically abused women reported being verbally abused as well, indicating that these forms of IPV were highly comorbid.ConclusionBoth verbal and physical IPV during pregnancy is associated with PPD in Japan. This is the first study investigating the impact of IPV on PPD using a large number of subjects in the country. Further study using the same participants of the current study would allow us to explore the causality between IPV during pregnancy and PPD.